Correlation of cognitive learning outcomes and creativity in PjBL with culturally responsive teaching - Ramadhani, Alfiah Putri; Subiantoro, Agung Wijaya (STKIP Persada Khatulistiwa Sintang, 2025)
Learning in the 21st century emphasizes higher-order thinking skills, particularly creativity and cognitive ability. However, observations in biology learning indicate that students’ creative thinking and conceptual understanding remain low, especially in biotechnology material. This study aims to determine the correlation between cognitive learning outcomes and creativity through the implementation of the Project-Based Learning (PjBL) model with the Culturally Responsive Teaching (CRT) approach. The research employed a quantitative correlational design involving 72 students of Grade X at SMA Negeri 1 Depok, Sleman, Yogyakarta. Data on creativity were collected using a validated creativity rubric, while cognitive learning outcomes were obtained from post-test scores. Data were analyzed using the Pearson product-moment correlation test with SPSS. The results showed that there was no significant correlation between cognitive learning outcomes and creativity (r = 0.090; p = 0.455 > 0.05). This finding suggests that an increase in cognitive learning outcomes does not necessarily lead to an increase in creativity. Thus, although the implementation of the PjBL-CRT approach contributed positively to students’ learning experiences, cognitive and creative abilities tended to develop independently. These results suggest the need for further learning strategies that explicitly integrate creative processes into cognitive learning tasks in biotechnology education.